Theoretical foundations for the study of ethnicity: organizational approach to the analysis of ethno-political conflicts - Isobchuk, M.V. (Perm Federal Research Centre Journal, 2022)
Despite the existence of many empirical studies aimed at clarifying the dynamics of ethnopolitical processes, a complete picture has not yet been formed. This is connected, among other things, with the fact that at present there is no consensus on the theoretical foundations of the study of ethnicity. Existing theoretical approaches not only directly contradict each other, but also do not provide the required epistemological tools for empirical analysis of ethnopolitical processes. In this article, on the basis of the genesis of the three main approaches to ethnicity - primordialism, instrumentalism and constructivism - an organizational approach to the study of ethnicity is proposed. It is assumed that it is the inclusion of ethnic organizations in the empirical analysis as the basic actors of ethnopolitical processes that can complement the existing concept of ethnicity. Internal (membership, goal, strategies, representative ability, etc.) and external (characteristics of the constellation of all resident organizations of an ethnic group, their interaction) parameters of an ethnic group, together with institutional and sociocultural characteristics, can increase the explanatory power of existing models of the dynamics of ethnopolitical processes. Thus, it is supposed to supplement the existing theoretical framework for the study of ethnicity and ethno-political processes in the modern world.